Digital camera calibration for cultural heritage documentation: the case study of a mass digitization project of religious monuments in Cyprus - Evagorou, Evagoras S.; Mettas, Christodoulos; Agapiou, Athos; Themistocleous, Kyriacos; Papavasileiou, Spyridon; Hadjimitsis, Diofantos G. (My University, 2021)
The paper summarizes the methodology followed, to evaluate the accuracy of different digitization methods of ecclesiastical monuments in 3D computer vision form and stresses the importance of photographic equipment calibration. In this study, a set of images were taken using the CANON EOS M5 digital camera, while the internal calibration parameters–horizontal and vertical focal length (fx, fy), principal point coordinates (x0, y0), radial distortion coefficients (K1, K2, K3), tangential distortion coefficients (P1, P2) and the affinity and the shear terms (b1, b2) were estimated. These parameters were calculated using different software applications and then analyzed. For the calibration procedure, 3D texture models were built with the Agisoft commercial software based on: (a) the aforementioned calibration parameters and (b) the self-calibration process. The overall accuracy (Root Mean Square–RMS) between these models, by comparing known geo-referenced ground-control-points (GCP) is presented through the Cloud Compare software. The results indicate that the internal calibration parameters of the digital camera used for documentation purposes are essential and should be systematically implemented for documentation purposes.
Keywords: Camera calibration; Cultural heritage; Lens distortion; Pre-calibration; Self-calibration